Analysis of corporate governance disclosure: a study on Brazilian companies - Oliveira, Marcelle Colares; Ceglia, Domenico; Lima, Lais Silva; Ponte, Vera Maria Rodrigues (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
This study aims to compare Brazilian legislation to United Nations’ international recommendation with respect to the influence of each on the disclosure level of Brazilian companies’ CG practices. The theoretical approach is institutional theory. It is an exploratory study because CG disclosure is an insufficiently studied phenomenon in the light of institutional theory. The research amounts to a qualitative but also a quantitative one since its procedures encompass content analysis techniques to collect data and statistical tools to analyze them. Data were collected from all the companies belonging to IBOV Index, an indicator of the average quotations of Brazilian stock market’s most traded, representative shares. It was concluded that coercive forces exert more influence on the disclosure of corporate governance by the Brazilian companies studied, which means legally required indicators were more disclosed than those simply recommended by United Nations.